PERGESERAN BENTUK PADA BUKU BILINGUAL SCIENCE BIOLOGY FOR JUNIOR HIGH SCHOOL GRADE IX - SUPRIADI SUPRIADI (STMIK KAPUTAMA, 2020)
Transposition has a very important role in the translation because the structure of the source language is often different from that the target language. By applying the transposition, then the translator can customize the translation in the target language with a more flexible and easier to read and understand. Without applying the transposition, a translation will be stiff and could even have no meaning because the structure is not adapted to the target language, and it may be very confusing for readers. This study aims at 1) describe the types of transposition that occur in a book translation Bilingual Science Biology for Junior High School Grade IX.